Corporate Social Responsibilty, Good Corporate Governance, Kinerja Lingkungan Terhadap Kinerja Keuangan Dan Pengaruhnya Pada Nilai Perusahaan: Corporate Social Responsibility, Good Corporate Governance, Environmental Performance on Financial Performance and Its Effect on Company Value - Maryanti, Eny; Fithri, Wildah Nihayatul (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this study wanted to identify the influence of corporate social responsibility, good corporate governance, and environmental performance to financial performance and identify the effect of the financial performance of the company's value. This study uses a quantitative method with path analysis technique, using a sample of companies listed on the Indonesian Stock Exchange and is also listed in the PROPER which consists of 16 companies with criteria determined sample through purposive sampling method. The results of this study is that CSR affect the financial performance of companies listed on the Indonesia Stock Exchange, this shows that CSR is done by the company in order to gain public confidence. GCG formed with institutional ownership and audit committee does not affect the company's financial performance. While GCG formed with managerial ownership, board of directors and independent directors significantly affect financial performance. The environmental performance does not significantly affect the company's financial performance. Managerial ownership, board of directors and independent directors indirectly through financial performance significantly affect the value of the company. Institutional ownership and audit committee indirectly through financial performance does not significantly affect the value of the company